From Knowledge to Character: Implementing the Axiological Values of Science in Student Character Formation - Dismawati; Muhammad Futaki Izhar; Nursalimah; Aprizon Dika Putra; Riska Meisyi Putri; Anggia Pratiwi; Efa Eriyani (Journal of Educational Management Research, 2026)
Education plays a vital role in developing students’ academic competencies and character in response to contemporary social and technological challenges. This study aimed to examine the implementation of the axiological values of science in learning and explore their contribution to student character formation. A qualitative approach with a case study design was employed. Data were collected through observations and in-depth interviews involving school leaders, teachers, students, and parents, and were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that axiological values are integrated into the educational process through classroom learning, habitual practices, teacher role modeling, and a values-oriented school culture. These practices contribute significantly to the development of students’ honesty, responsibility, discipline, cooperation, social awareness, and religiosity. The study also identifies several supporting factors, including teacher commitment, leadership support, a positive school culture, and parental involvement, while differences in family backgrounds and the influence of digital technology emerge as key challenges. The findings imply that integrating the axiological values of science into learning can serve as an effective strategy for fostering sustainable character development and promoting the ethical application of knowledge in students’ daily lives.